Potentiometric Studies and Modelization of Ternary Complexes of Nickel(II) with a Tetradentate Schiff-base and Its Reduced Form as the Primary Ligand and Methionine and Cysteine as the Secondary One - Belaid, S.; Djebbar, S.; Benali-Baitich, O.; Ghalem, S.; Khan, M.A.; Bouet, G. (Asian Journal of Chemistry, 2016)
The stability constants of binary and ternary complexes of nickel(II) with two tetradentate ligands: bis(2-hydroxyacetophenone) ethylenediamine (H2BS) and N,N´-bis(2-hydroxyacetophenyl)-1,2-diaminoethane (H2BSR) as primary ligands and two amino acids: methionine (Met) and cysteine (Cys) as secondary ones, were determined by potentiometric measurements at constant temperature (25.0 ± 0.1ºC) and ionic strength (0.2 mol L-1, NaCl) in water-ethanol (90 : 10 w/w) medium. Two species are formed for which the molar ratio of metal to BS or BSR and Met or Cys are 1 : 1 : 1 and 1 : 1 : 2. The binary and ternary complexes of BSR are more stable than those of BS. The values of D log K constant show that ternary complexes have a higher stability than the corresponding binary ones in the case of methionine but not for cysteine. The geometry of all the species formed have been optimized by molecular mechanics using the EMO program. It was found that there is a direct correlation between the stability constants of the ternary complexes and their steric energy.